Surrogate definition and homogeneous chemical kinetic model for two alkane-rich FACE gasoline fuels. Issue 2 (4th March 2019) - Yu, Jin; Wang, Zijun; Zhuo, Xiaofang; Gou, Xiaolong
Abstract : A surrogate formulation methodology is proposed by directly using functional groups C H 3, C H 2, CH, C and phenyl to build the surrogate models for the FACE (fuels for advanced combustion engines) A and C gasoline fuels. The surrogates were formulated with the mixture of n -butane/ n -heptane/iso-octane/2, 5-dimethylhexane for FACE A, and with the mixture of n -butane/ n -heptane/iso-octane/2, 5-dimethylhexane/toluene for FACE C gasoline fuel. Based on the kinetic mechanisms of the candidate components, the surrogate fuel models were assembled through a hierarchical construction way. In order to get a simpler surrogate model, the detailed mechanism of 2, 5-dimethylhexane has been reduced by the path flux analysis (PFA) method and optimised by updating the reaction rate constants of selected reactions before the surrogated fuel model construction. Thereafter, the accuracy of the surrogate models was demonstrated by comparing the model predictions against ignition delay measurements for FACE A and C gasoline fuels in a wide range of conditions (10–40 bar; 0.5–1 equivalence ratios), and the results show that the presented surrogate fuel models can reproduce the ignition behaviours better especially in the low-temperature conditions. The surrogate chemical kinetic model construction method can be used in other fuels to get simpler and lower computational cost surrogate fuel models.